Applying Expectancy-Value Theory to Understand Investment Interest in the Young Generation - Arfin Haryono; Muhammad Fadlul; Ina Septiana (Fundamental and Applied Management Journal, 2024)
This study aims to explore the investment interest of students at Universitas Negeri Makassar (UNM) through the lens of Expectancy-Value Theory (EVT). The research examines how students' expectations and perceived value influence their interest in investing. Data were collected from a sample of UNM students, and the findings indicate that both expectancy and value have a positive and significant impact on their investment interest. This suggests that enhancing students' expectations and perceptions of the value of investment could lead to a greater interest in investing. The study employed a quantitative approach using SPSS for data analysis. The results reveal that students' investment decisions are strongly influenced by their perceptions of task difficulty, effort, behavioral attitudes, and subjective norms. Additionally, motivation and self-confidence play crucial roles in shaping their investment interest. These findings have important implications for educational strategies, highlighting the need to foster a supportive environment that builds students' confidence and enhances their understanding of the benefits of investing. By doing so, educators can encourage students to develop a stronger interest in and commitment to investment activities.